Highly Reliable Label-Free Detection of Urea/Glucose and Sensing Mechanism Using SiO2 and CdSe-ZnS Nanoparticles in Electrolyte-Insulator-Semiconductor Structure. Issue 13 (16th September 2016) - Kumar, Pankaj; Maikap, Siddheswar; Singh, Kanishk; Chatterjee, Subhodeep; Chen, Yi-Yan; Cheng, Hsin-Ming; Mahapatra, Rajat; Qiu, Jian-Tai; Yang, Jer-Ren
Abstract : A simple, label-free and cost effective sensor have been studied for reliable urea/glucose sensing, and common serum analyte detection comparable with market available urea "Assay Kit" is also performed by using SiO2 and CdSe-ZnS nanoparticles in electrolyte-insulator-semiconductor structure for the first time. Thermally grown SiO2 membrane has shown lower pH detection limit (0.081) and lowest drift rate (2.9 mV/hr) than those of the sputtering and E-beam deposited SiO2 membranes. The urea detection at physiological buffer pH 7.4 with sensitivity of ∼1.6 mV/mg.dl −1 at linear range of 6 to 36 mg/dl is shown. The pH detection limit is further reduced (0.074) by using chaperonin protein mediated CdSe-ZnS nanoparticles assembly over SiO2 surface owing to high pH sensitivity of 55 mV/pH. The sensing mechanism is due to the SiOx content decreased with increasing pH value. This suggests the lower H + ions absorption on the sensing membrane surface, which is observed by X-ray photo-electron spectroscopy. The glucose concentration is detected by using the core-shell CdSe-ZnS nanoparticles through H2 O2 sensing because of reduction/oxidation (redox) properties of Zn as well as Zn 2+ ions generation. Due to the high catalytic activity for H2 O2 sensitivity, low detection limit of 1 μM is obtained, which will help to detect glucose using this bio-chip in future.